Perlindungan Hadhanah Akibat Perkawinan Beda Agama di Indonesia: Perspektif Hukum Islam - Abel Sulaeman; Ni Made Jaya Senastri; Indah Permatasari (Mutawasith: Jurnal Hukum Islam, 2026)
Interfaith marriages in Indonesia present complex legal challenges, particularly in divorce cases that impact the allocation of child custody (hadhanah). Divergent interpretations based on Marriage Law and the Islamic Legal Compilation (KHI) often create uncertainty for judges and dilemmas in determining custody, especially regarding ḥifẓ al-dīn alongside the application of standards prioritizing childs protection. The research investigates a legal validity on interfaith marriages according to both the Marriage Law and KHI, while also assessing the legal certainty surrounding child custody in cases of interfaith divorce from an Islamic law perspective. The study adopts a normative legal methodology, incorporating statute-based, case-based, and conceptual approaches. Data are gathered and analyzed through a literature review using primary, secondary, and tertiary sources. The results reveal that cross faith marriages were not acknowledged as recognized by either Islamic or national law, and that child custody arrangements in such divorces emphasize the best interests of the child, with religious safeguarding (ḥifẓ al-dīn) being a core element of a (maqāṣid al-shari‘ah).